Poor prognosis after surgery for intertrochanteric fracture in elderly patients with clopidogrel treatment: A cohort study. Issue 39 (September 2017) - Zhang, Jianzheng; Chen, Xiaobin; Wang, Juan; Liu, Zhi; Wang, Xiaowei; Ren, Jixin; Sun, Tiansheng
Abstract : Abstract: Choice of surgical approach in patients under clopidogrel treatment is controversial. Intertrochanteric fractures are common in the elderly, who also suffer from a number of comorbidities. The aim of this study is to assess the prognosis of elderly patients with clopidogrel treatment after surgery for intertrochanteric fracture. This was a cohort study of 238 elderly patients who underwent proximal femur intramedullary nailing for intertrochanteric fracture between January 2012 and December 2013 at the Geriatric Trauma Center of the Beijing Army General Hospital. The patients were divided into the clopidogrel (n = 32) and control (n = 206) groups according to their history of long-term clopidogrel treatment before surgery. Demographic and clinical characteristics, intraoperative parameters, postoperative complications, and 1-year survival were compared between the 2 groups. Preoperative American Society of Anesthesiologists (ASA) grade and the frequency of arterial stenting were different between the 2 groups ( P = .002 and P < .001, respectively). The rate of intraoperative blood transfusion, ICU stay, and hospital stay were higher in the clopidogrel group compared with the control group (all P < .001). Postoperative complications were similar in the 2 groups. The 1-year mortality rate after surgery was significantly higher in the clopidogrel group compared with the control group (37.5% vs 20.3%, P = .030). Prognosis after surgery for intertrochanteric fracture was poorer in elderly patients with clopidogrel treatment; these patients had lower 1-year survival, more intraoperative blood transfusion, longer ICU stay, and longer hospital stay. ASA grade, arterial stenting, and anesthesia mode were prognostic factors.